Continuous planting Eucalyptus plantations in subtropical China: Soil phenolic acid accumulation and adsorption physiognomies - Saif Ullah; Saif Ullah; Yuanyuan Xu; Yuanyuan Xu; Chengrui Liao; Wannian Li; Wannian Li; Fei Cheng; Fei Cheng; Shaoming Ye; Shaoming Ye; Mei Yang; et al. (Frontiers in Forests and Global Change, 2023)
As phenolic acids accumulated in monocropping plantations, their allelopathic effects caused the soil’s fertility to decline and productivity to decrease. The effects of stand age and generational turnover of phenolic acids in soil remain unclear. Therefore, we conducted an experiment to examine the changes in phenolic acid content and accumulation characteristics in soils from Eucalyptus plantations in terms of planting years and generations. Soils were collected from three Eucalyptus plantations: a 6-year-old first-generation plantation (6a1g), 9-year-old first-generation plantation (9a1g) and 6-year-old second-generation plantation (6a2g). Seven phenolic acids were identified from different soil samples by high-performance liquid chromatography. In addition, exogenous phenolic acids were added to the soil samples to study the kinetics as well as the adsorption and desorption characteristics of soils. The total of seven phenolic compounds in 6a1g (38.451 μg g–1) was higher than that of the 9a1g and 6a2g soils, and the total of 6a2g (27.257 μg g–1) was higher than that of the 9a1g (15.536 μg g–1). In the tested soil, the p-hydroxybenzoic acid accounted for 51.6% (for 6a1g), 51.1% (for 9a1g) and 33.5% (for 6a2g) of the total amount of the seven phenolic acids, the p-hydroxybenzoic may have had a higher allelopathic capacity in these Eucalyptus plantation soils. Soil bulk density showed a strong positive correlation with vanillic and ferulic acids, and SOM also had an extremely positive correlation with p-hydroxybenzoic and coumalic acids. The findings demonstrated that the adsorption and desorption rates and amounts of each phenolic acid in the soil of 6a1g were higher than those in the soil of 9a2g and 6a2g using both a kinetic adsorption experiment and isothermal adsorption and desorption experiments. But among the three soils, 9a1g soil had the lowest adsorption rate, which resulted in the lowest accumulation capacity. It is noticed that the Pseudo-second-order kinetic model can be used to describe the kinetic adsorption better than the Pseudo-first-order kinetic model and the Elovich model, and the Freundlich model could fit the desorption isotherms better than the adsorption isotherms. However, more study of this phenomenon is essential to better understanding its mechanisms and how they function in order to address issues with soil degradation in future intergenerational Eucalyptus plantings.